KONTRIBUSI PAJAK REKLAME DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KOTA SURABAYA - Sulistiyoningsih, Sulistiyoningsih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out how much the contribution of advertisement tax to the local own-source revenue and efforts which have been performed by the Surabaya city government in order to increase tax revenue of Surabaya city. The result of the research shows that the management of advertisement tax in Surabaya city is less optimal. It can be seen from the contribution of advertisement tax to the average local own-source revenue in 2008-2012 is only 7.45% or very low in criteria. The average contribution of advertisement tax to the local tax is 12.26% or in low criteria. While from the effectiveness point of view, it has been found that the management of advertisement tax is in quite effective criteria.Keywords: Advertisement Tax, Contribution, Local Own-Source Revenue